KONSISTENSI NOTARIS DALAM PEMBUATAN PERJANJIAN KAWIN TERHADAP PERKAWINAN YANG SEDANG BERLANGSUNG (STUDI AKTA PERJANJIAN PERKAWINAN NOMOR 76 TERTANGGAL 21 JULI 2022) - Sausan Raihanah Siregar; Tengku Keizerina Devi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Marriage agreements before the Constitutional Court decision Number 69/PUU-XIII/2015 were only made at or before the marriage took place. However, after the issuance of the Constitutional Court decision Number 69/PUU-XIII/2015 Article 29 paragraph (1), marriage agreements no longer have to be made before or on the day of the marriage, but husband and wife can make a marriage agreement while they are married. This study discusses the obligations of a Notary in carrying out his/her position regarding requests to make a Deed of Marriage Agreement by a husband and wife, the position of separation of assets of a husband and wife who make a marriage agreement in deed number 76 dated 21 July 2022, as well as the consistency of the Notary in implementing legal regulations in making marriage agreement deed number 76 dated July 21 2022. Keyword: Marriage Deed Agreement, Notary Consistency, Marriage Agreement Abstrak: Perjanjian perkawinan sebelum adanya putusan MK Nomor 69/PUU- XIII/2015, hanya dibuat pada waktu atau sebelum perkawinan dilangsungkan. Akan tetapi, pasca keluarnya putusan MK Nomor 69/PUU-XIII/2015 Pasal 29 ayat (1) perjanjian perkawinan tidak lagi harus dilakukan pada saat sebelum atau pada saat hari dilangsungkannya perkawinan, melainkan pasangan suami istri dapat membuat perjanjian perkawinan selama dalam ikatan perkawinan. Kajian ini membahas mengenai bagaimana kewajiban Notaris dalam menjalankan jabatannya terhadap permintaan pembuatan Akta Perjanjian Perkawinan oleh sepasang suami istri, kedudukan pemisahan harta pasangan suami-istri yang membuat perjanjian perkawinan dalam akta nomor 76 tertanggal 21 Juli 2022, serta konsistensi Notaris dalam menjalankan peraturan perundangan pada pembuatan akta perjanjian perkawinan nomor 76 tertanggal 21 Juli 2022. Kata kunci: Perjanjian Kawin, Konsistensi Notaris, Akta Perjanjian Perkawinan